2017
DOI: 10.3390/ijgi6060166
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge-Driven Geospatially Enabled Framework for Geological Big Data

Abstract: Geologic survey procedures accumulate large volumes of structured and unstructured data. Fully exploiting the knowledge and information that are included in geological big data and improving the accessibility of large volumes of data are important endeavors. In this paper, which is based on the architecture of the geological survey information cloud-computing platform (GSICCP) and big-data-related technologies, we split geologic unstructured data into fragments and extract multi-dimensional features via geolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…They cover a variety of topics about geological survey, ranging from ore/deposits, mineral, remote sensing, to geology, hydrology. Many types of entities are also mentioned in various geological reports, which include not only significant locations, but also rocks, minerals, to stratigraphic units, locations, geological timescales (Fan et al., 2020; Qiu, Xie, Wu, Tao, & Li, 2019; Qiu, Xie, Wu, & Tao, 2019; Wang et al., 2021; Wu et al., 2017). Named entity recognition (NER) has received much attention from the academic field and industry for many years (Nieh et al., 2021; Qiu, Xie, Wu, Tao, & Li, 2019; Qiu, Xie, Wu, & Tao, 2019; Zhou et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They cover a variety of topics about geological survey, ranging from ore/deposits, mineral, remote sensing, to geology, hydrology. Many types of entities are also mentioned in various geological reports, which include not only significant locations, but also rocks, minerals, to stratigraphic units, locations, geological timescales (Fan et al., 2020; Qiu, Xie, Wu, Tao, & Li, 2019; Qiu, Xie, Wu, & Tao, 2019; Wang et al., 2021; Wu et al., 2017). Named entity recognition (NER) has received much attention from the academic field and industry for many years (Nieh et al., 2021; Qiu, Xie, Wu, Tao, & Li, 2019; Qiu, Xie, Wu, & Tao, 2019; Zhou et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It means an urgent need to improve information extraction, knowledge mining, and knowledge association in heterogeneous geological data (Li & Shao, 2009). Recent studies have shown that the performance of downstream tasks for text mining, such as partā€ofā€speech tagging, retrieve text from images (Shao et al., 2020; Zhou et al., 2017) and named entity recognition (Ma et al., 2018; Qiu et al., 2018, 2019; L. Wu et al., 2017), strongly depends on high precision geological word segmentation methods. This is because all of these downstream tasks, beside the extraction of multiā€level and multiā€dimensional image features required in retrieving text from images, require the system to have a good understanding of the text, which is the cornerstone of Chinese word segmentation (CWS).…”
Section: Introductionmentioning
confidence: 99%
“…The textual content from studies is recorded and presented in a variety of types, such as journal papers, technical documents/reports, and monographs and books (Huang et al, ). Many national geological survey agencies focus on handling georeferenced quantitative data/information, including rock structures, geochemical anomalies, satellite imagery, and geophysical surveys (Qiu et al, ; Wu et al, ). As a key component of open and published data, geoscience documents/reports often contain potential and valuable information for further research (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%